The impact of voice recording as a mobile assisted language learning strategy in the development of utterance fluency during speaking tasks in ninth grade students at Liceo Experimental Bilingüe de Turrialba - Brenes Soto, Angeline 1993- (2023)
The present research will analyze the impact of technology use, specifically mobile phones' default Voice Recordings where students can practice speaking in English by recording themselves speaking and teachers could measure utterance fluency based on pausing. At the end of the treatment, it is going to be discussed if this tool is effective to help students to improve their fluency, so teachers can use this technique in their classes since speaking English fluently and having a good proficiency level is an important aspect in our country.